Lipomatous hypertrophy of the interatrial septum - Rodrigues, H (2005)
Authors describe a case of Lipomatous hypertrophy of the interatrial septum diagnosed by MR. A mass in right atrium with 18cm2 was detected by echocardiography, and later MR showed a homogeneous mass, with high intensity in T1 images and a decrease of signal with fat-suppression.